Sequence variability of bovine leukemia virus env gene and its relevance to the structure and antigenicity of the glycoproteins. - Mamoun, R Z (1990)
The nucleotide sequences of the env genes of seven bovine leukemia viruses and the encoded peptide sequence were compared, with the objective of (i) determining the genetic distance separating bovine leukemia virus isolates from different geographical regions, (ii) identifying particular amino acids that contribute to the sequential and conformational epitopes, and (iii) relating such epitopes to their projected position in a three-dimensional model of the structure of the gp51 surface glycoprotein. Two bovine leukemia virus subgroups were clearly identified, a Japanese-American subgroup represented by strains lambda BLV-1, VdM, and FLK-BLV and a European subgroup by strains T15-2, LB285, and LB59. It was possible to identify amino acids that were important in determining three of the epitopes (F, G, and H) recognized by neutralizing monoclonal and polyclonal antibodies. On the model, these epitopes were adjacent and located on the exposed region of the molecule. Amino acid sequences contributing to a fourth cryptic epitope were identified; as predicted by the model, they lay on the opposite side to the neutralizable epitopes in a region involved in glycoprotein subunit association. The fact that this region is not normally exposed on the virion surface provides further evidence for the validity of the model.